2018
DOI: 10.1007/s10571-018-0618-1
|View full text |Cite
|
Sign up to set email alerts
|

Allopregnanolone and Progesterone in Experimental Neuropathic Pain: Former and New Insights with a Translational Perspective

Abstract: In the last decades, an active and stimulating area of research has been devoted to explore the role of neuroactive steroids in pain modulation. Despite challenges, these studies have clearly contributed to unravel the multiple and complex actions and potential mechanisms underlying steroid effects in several experimental conditions that mimic human chronic pain states. Based on the available data, this review focuses mainly on progesterone and its reduced derivative allopregnanolone (also called 3α,5α-tetrahy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 186 publications
0
23
0
Order By: Relevance
“…Notably, ALLO synthesized by SCs might attain efficient concentration in the narrow space between SC membrane and axon, both in myelinated fibers (i.e., in the periaxonal/adaxonal space) and in unmyelinated fibers (i.e., Remak bundles). The observation that ALLO serves as an autocrine factor in SCs is not new, since it was already demonstrated that ALLO enhances the glutamic acid decarboxylase (GAD) expression/activity and subsequently GABA synthesis in SCs [ 13 , 15 ]. Interestingly, ALLO has been proposed as a possible pharmacological treatment for nerve degenerative diseases [ 10 , 11 , 14 , 15 , 39 ] and hyperalgesia [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, ALLO synthesized by SCs might attain efficient concentration in the narrow space between SC membrane and axon, both in myelinated fibers (i.e., in the periaxonal/adaxonal space) and in unmyelinated fibers (i.e., Remak bundles). The observation that ALLO serves as an autocrine factor in SCs is not new, since it was already demonstrated that ALLO enhances the glutamic acid decarboxylase (GAD) expression/activity and subsequently GABA synthesis in SCs [ 13 , 15 ]. Interestingly, ALLO has been proposed as a possible pharmacological treatment for nerve degenerative diseases [ 10 , 11 , 14 , 15 , 39 ] and hyperalgesia [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…ALLO is produced by SCs, since these cells possess the biosynthetic enzymatic complex [ 9 , 10 , 11 ]. In the PNS, ALLO participates in the control of myelination, nerve regeneration [ 9 , 12 , 13 , 14 ] and also nociception [ 15 ]. ALLO capacity to modulate nociceptive pathways has long been ascribed to its allosteric activation of the GABA type A (GABA A ) receptor, thus potentiating its inhibitory role, at least in central nervous system (CNS) synapses [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, well known are the anti-allodynic effects exerted by PR and its reduced metabolite allopregnanolone, neuroactive steroids with proven neuroprotective and anti-inflammatory actions, 11,12 in different animal models of neuropathic pain. [36][37][38][39] In particular, we have recently shown that early and sustained PR administration to animals with a sciatic nerve chronic constriction injury 40 or a spinal cord hemisection 13,14,21 is able to avoid maladaptive changes leading to central sensitization, thus preventing the development of mechanical and thermal allodynia. 13,14,21,40 However, PR-delayed treatment was not able to suppress well established allodynia, at least after a sciatic nerve constriction 41 or a spinal cord hemisection.…”
Section: Discussionmentioning
confidence: 99%
“…13,65 Although these mechanisms have not yet been studied in the presence of HPGC, it would be feasible to postulate their participation in the effects here observed, and will be the subject of future studies. In fact, both neurons and glial cells of the peripheral and central nervous system express PR 36,37 and GR, 67 making these cells sensitive targets to HPGC actions.…”
Section: Discussionmentioning
confidence: 99%
“…Intracerebroventricular administration of allopregnanolone has analgesic effects in naïve male rats (Kavaliers and Wiebe, ). Likewise, systemic and intrathecal administration of allopregnanolone, or its precursor progesterone, exerts antinociceptive properties in several models of neuropathic (see Gonzalez and colleagues () for review) and inflammatory pain (Ocvirk et al, ). Thus, administration of neuroactive steroids might be beneficial to ameliorate pain symptoms.…”
Section: Alcohol Addiction Results From Excessive Proinflammatory Neumentioning
confidence: 99%